2016
DOI: 10.1111/1346-8138.13483
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the drug resistance‐determining region of Mycobacterium lepromatosis isolated from leprosy patients in Mexico

Abstract: Mycobacterium lepromatosis, an independent species from Mycobacterium leprae, has been found to be a causative agent for diffuse lepromatous leprosy (DLL) in Mexico, but remains poorly studied. Here, the drug resistance-determining regions (DRDR) of folP1, rpoB and gyrA (conferring resistance to dapsone, rifampicin and quinolone, respectively) in M. lepromatosis from leprosy patients in Mexico were characterized. No mutations or silent mutations were found at previously characterized major sites in DRDR of M. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The finding of 4 cases with M. lepromatosis infection from 82 relapsed cases strongly indicates that this mycobacterial species is also prevalent in India. Kai et al 19 also reported similar findings after analysis of biopsies obtained from 19 lepromatous cases from Mexico. As the present study was limited to a few selected samples, the data is not suitable to provide data on the actual prevalence of leprosy caused by this mycobacterial species in the country.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The finding of 4 cases with M. lepromatosis infection from 82 relapsed cases strongly indicates that this mycobacterial species is also prevalent in India. Kai et al 19 also reported similar findings after analysis of biopsies obtained from 19 lepromatous cases from Mexico. As the present study was limited to a few selected samples, the data is not suitable to provide data on the actual prevalence of leprosy caused by this mycobacterial species in the country.…”
Section: Discussionmentioning
confidence: 55%
“…In the recent past, many studies/case reports have been described with clinical presentations matching very closely those in Lucio phenomenon from other parts of the world, like Brazil and Malaysia, along with confirmation based on molecular findings. 18 , 19 The present study was carried out to assess the prevalence of newly discovered bacteria in DLL patients from India. For the first time, using specific DNA sequences, the presence of M. lepromatosis in diffuse LL has been reported in India.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent case reports indicated that M. lepromatosis was not related specifically to DLL, but also with other multibacillary forms of HD. Dual infection with M. lepromatosis and M. leprae has also been reported in case reports from South America (Aldama Olmedo et al, 2020) and South East Asia (Han et al, 2012a;Widiatma and Sukanto, 2019) and in surveys of specimens from Mexico and Brazil (Han et al, 2012b(Han et al, , 2014Kai et al, 2016;Torres-Guerrero et al, 2018;Sharma et al, 2020). Medical and scientific literature refers to both species as the causal agents of HD, but cases attributed to M. lepromatosis infection are infrequently reported, and the clinical aspects of HD caused by M. lepromatosis remain poorly characterized.…”
Section: Introductionmentioning
confidence: 94%
“…Finally, none of these studies reported antibiotic resistance pattern of M. leprae. There are reports on drug resistance in leprosy patients [45][46][47][48][49] and can be one of the reasons of the relapse rate increase in the last years [50]. Considering some of the areas with leprosy had also high incidence of resistant tuberculosis (such us India) and MDT share rifampin as an important drug with sensitive tuberculosis, closer follow-up and drug resistance studies should be done in these areas.…”
Section: Limitations and Strengthsmentioning
confidence: 99%